Basis of Virulence in Enterotoxin-Mediated Staphylococcal Food Poisoning - Fisher, Emilie L.; Otto, Michael; Cheung, Gordon Y. C. (Frontiers in Microbiology, 2018)
The Staphylococcus aureus enterotoxins are a superfamily of secreted virulence factors that share structural and functional similarities and possess potent superantigenic activity causing disruptions in adaptive immunity. The enterotoxins can be separated into two groups; the classical (SEA-SEE) and the newer (SEG-SElY and counting) enterotoxin groups. Many members from both these groups contribute to the pathogenesis of several serious human diseases, including toxic shock syndrome, pneumonia and sepsis-related infections. Additionally, many members demonstrate emetic activity and are frequently responsible for food poisoning outbreaks. Due to their robust tolerance to denaturing, the enterotoxins retain activity in food contaminated previously with S. aureus. The genes encoding the enterotoxins are found mostly on a variety of different mobile genetic elements. Therefore, the presence of enterotoxins can vary widely among different S. aureus isolates. Additionally, the enterotoxins are regulated by multiple, and often overlapping, regulatory pathways, which are influenced by environmental factors. In this review, we also will focus on the newer enterotoxins (SEG-SElY), which matter for the role of S. aureus as an enteropathogen, and summarize our current knowledge on their prevalence in recent food poisoning outbreaks. Finally, we will review the current literature regarding the key elements that govern the complex regulation of enterotoxins, the molecular mechanisms underlying their enterotoxigenic, superantigenic, and immunomodulatory functions, and discuss how these activities may collectively contribute to the overall manifestation of staphylococcal food poisoning.